Pengaruh Kepemimpinan, Beban Kerja, Dan Kompensasi Terhadap Turnover Intention Karyawan (Studi Kasus Karyawan Pada PT. Natura Laboratoria Prima) - Ginanjar Arif Santoso; M. Sulhan (FEB Universitas Maritim Semarang, 2023)
This study aims to determine the effect of leadership, workload, and compensation on employee turnover intention. This type of research is quantitative, and the analysis used involves associations with a quantitative approach. Research conducted at PT. Natura Laboratoria Prima. The study results show that leadership has a detrimental and important impact on the intention to change jobs. The superior leadership proportionally reduces the intention to change jobs. The workload level positively and significantly impacts the intention to change jobs. The greater the workload, the higher the intention to change jobs. Compensation has an adverse and important impact on the intention to change jobs employees of PT. Natura Laboratoria Prima, meaning that the higher the compensation, the lower the turnover intention.